Helicobacter pylori (HP) serology: an audit of action on positive serology results. (13th March 2011) - James, B; Srinivas, M; Willemse, P; Basumani, P; Hoeroldt, B; Bardhan, K
Abstract : Introduction: Hp causes peptic ulcer disease (PUD) and is potentially carcinogenic. Hp eradication is done in conditions like PUD, uncomplicated dyspepsia and persistent iron deficiency anaemia. 'Test and treat' implies testing specifically with intent to treat, if positive. CLO test is read in real time and acted on promptly. Hp serology is used in acute upper GI (UGI) bleed or endoscopy on PPI as CLO test is less sensitive. Results take 5–7 days by when in-patients have been discharged and positive Hp serology (Hp+ve) results overlooked. This audit was prompted by two such missed cases of Hp+ve PUD with rebleed in one. Aim: To review action taken on Hp+ve results in our hospital, assess factors contributing to inaction, impact on patient care and remedial steps needed. Methods: Retrospective study of all patients with Hp+ve requested by hospital clinicians in 12 months (1 April 2009 to 31 March 2010). Serology data from our microbiology department was matched with subsequent urea breath tests (UBT), our standard test to confirm eradication. Patients with sequential serology and UBT were deemed to have received eradication. Case notes of the others were reviewed for test indication, point of first contact, gastroscopy findings (if done), eradication recommendation by endoscopist, specialist nurse (SpN) contact, reason for non-eradication and any complications. Conclusion: 1 in 6 Hp+ve not eradicated; 21/33 results not reviewed. Factors for inaction: multiple test sources (clinic, ward, endoscopy), lack of single contact of point (poor use of SpN support), unclear advice from endoscopists. Recommendations: In routine clinical practice, test Hp serology only with intent to treat positives. SpN in endoscopy unit to be single point for contact, review of results and action on Hp+ve results: If +ve, initiate and ensure successful eradication where recommended; contact clinician to decide for eradication or not, in the rest. Local arrangements made for lab to send copy of all hospital initiated Hp+ve results to SpN for above action.